How (sustainable) business model patterns help initiating design for sustainability - Leandro Bitetti; Mattia Bedolla (Journal of Business Models (JOBM), 2024)
This study explores the cognitive impact of sustainable business model patterns on initiating design for sustainability, comparing them to traditional patterns. Utilizing a quasi-experimental design with four teams of Master's students in Innovation Management, we assessed how the type of business model pattern cards influences cognitive processes and idea generation during ideation. Our findings demonstrate that sustainable business model patterns significantly enhance cognitive stimulation, promoting a broader perspective on sustainability issues. They excel in integrating all three dimensions-economic, ecological, and social-of sustainable business model innovation within the context of idea generation. This research bridges interpretations of business models as (1) cognitive schemas and (2) formal representations, highlighting the pivotal role of specific visual tools in facilitating sustainable business model innovation. This includes challenging cognitive barriers and fostering a comprehensive approach to sustainable design.
Keywords: 650; sustainable business model innovation; business model patterns; cognition